Inventory of threatened plants of Bangladesh and their conservation management - Harun-ur-Rashid, M; Rashid, M Enamur; Rahman, M Atiqur (International Journal of Environment, 2014)
The study aimed at inventorying of threatened plant species of Bangladesh to determine their status of occurrence for emphasizing the setting-up of national conservation strategies and sustainable management. Complete inventory of two families, the Apocynaceae and Vitaceae, has been made and recognized 28 threatened species facing environmental threats, and need sustainable conservation management. The study was based on long-term field investigation, survey of relevant floristic literature and examination of herbarium specimens. An enumeration of threatened taxa is prepared with updated field data on conservation status to include into Red Data Book of Bangladesh. DOI: http://dx.doi.org/10.3126/ije.v3i1.9951 International Journal of Environment Vol.3(1) 2014: 141-167